Ransomware attacks in the United States : Analysis, Mitigation, and Recovery strategies - Miska, Kristina (2024)
In our digitally dominant era, cybersecurity is one of the biggest concerns. Ransomware attacks are changing and becoming even more frequent as technology evolves, turning into one of the biggest cyberthreats, with various effects and impacts on their victims such as financial loss, data loss, operational issues, and many more. The rise of digital infrastructure has brought a growing proneness to ransomware attacks specially in sectors like healthcare, education and finance, with the United States being one of the most targeted countries worldwide. The financial gain that ransomware attacks promise, as well as several other motives, have given the attackers a chance to raise this cyberthreat, causing significant damage in most of the cases. This master's thesis is dedicated to a comprehensive exploration of ransomware attacks, shedding light on their evolution and exploring their impact on these three different sectors. Using a mixed-methods approach, that includes primary data from a survey, with 154 participants, as well as complementary data from industry-specific reports and publications, the study aims to identify trends in ransomware attacks and provide a better understanding of how things have been changing over the last five years. The study results, among others, in significant financial and operational impacts such as expensive downtime, data loss and negative impact on organisational reputation, as well as difficulties in recovering. It shows that healthcare sector is the most vulnerable, while financial sector leads in monetary losses and educational sector faces significant long-term impacts. The study among others emphasises the importance of incident response planning, employee awareness and training, as well as the need for synchronised collaborative efforts to combat face such challenges.